The Effectiveness and Sustainability of the Saemaul Undong's Participatory Approach in Rural Cambodia - Bunra Hun (Journal of General Education and Humanities, 2025)
This study addresses the challenge of fostering sustainable rural development and effective local governance in Cambodia by evaluating the applicability and impact of the Saemaul Undong (SMU) leadership model, originally developed in South Korea. Specifically, it investigates how the SMU model enhances community participation and leadership effectiveness within the dynamic contexts of decentralization reforms and post-conflict reconstruction in rural Cambodia. A mixed-methods research design was employed. Data collection involved a combination of qualitative approaches (interviews, focus groups) and quantitative methods (structured questionnaires, statistical analysis) across 12 strategically selected SMU pilot villages in Kampong Speu, Tboung Khmum, and Takeo provinces, in addition to insights from the Cambodia-Korea Rural Development Center (CKRDC). Quantitative data was analyzed using SPSS, incorporating descriptive statistics, regression modeling, and path analysis. Findings reveal significant positive outcomes, with a high commitment to SMU activities reflected by 98.9% of respondents expressing continued involvement. Statistical analysis demonstrates strong positive and statistically significant correlations between SMU training and key development indicators: women’s leadership (r = .896), community participation (r = .862), and income generation (r = .799). SMU principal training emerged as the most influential factor, followed by practical application and knowledge acquisition, in driving these improvements. The study highlights the model’s capacity to reinforce local governance and decentralization efforts by developing capable and participatory leadership at the community level.